APLIKASI PUPUK ORGANIK DAN BENZILADENIN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN ROSELA (Hibiscus sabdariffa L.) - Budi Santoso; Irsal Irsal; Haryati Haryati (Universitas Sumatera Utara, 2013)
This research has been conducted to study the effect of organic matter andbenziladenin aplication on the growth and yield of the roselle. Research wasconducted on Research Center at Tanjung Selamat Village, sub district sunggalwith a height of 57 m above sea level during February-June 2012, using factorialrandomized block design with two factors, they are compost (0, 200, 400g/polybag) and benziladenin (0, 100, 200, 300 cc/l). The parameters observedwere plant height, flowering age, branch number, fruit production per plant, freshweight of fruits per plant, fresh weight of petals per plant, dry weightof petals perplant and seed weight per plant. The result of the research showed that compostsignificantly increased all parameters, bensiladenin significantly increased thebranch number, and interaction of both compost and benziladenine did not showany significant effect on all parameters.